Ethics, Bounded Rationality, and IP Sharing in IT Outsourcing - Anand, Krishnan S.; Goyal, Manu (Management Science, 2019)
Our dynamic model of information technology (IT) outsourcing integrates incomplete contracts, moral hazard, and adverse selection under both perfect and, more realistically, bounded rationality. In addition to the classical profit-maximizing firm unconstrained by ethics, we model an ethically constrained (but otherwise profit-maximizing) firm that honors its contractual obligations irrespective of legal restraints. We prove that under bounded rationality, the ethically constrained firm can obtain strictly greater profits than the unconstrained profit-maximizing firm, even when (i) the unconstrained firm has access to a superset of the ethical firm’s strategies and (ii) the ethical firm is unable to reveal its ethical commitment to its contracting partner anytime during the contractual relationship. Thus, a commitment to ethics, while of course being morally desirable, can lead to higher profits than the unbridled profit-maximization of classical economics. We also prove that ethics is foundational to both intellectual property (IP) sharing and reputation effects, two well-known facilitators of IT outsourcing. In fact, the mere possibility of ethical firms (a) forces across-the-board IP sharing even if it lowers profits and (b) induces even an ethically unconstrained firm to invest in developing a reputation for ethics. Our model provides a novel explanation, rooted in ethics, for why IT outsourcing is booming despite the formidable impediments of incomplete contracts, moral hazard, and adverse selection. This paper was accepted by Anandhi Bharadwaj, information systems.